Performing baroque music - Cyr, Mary (Amadeus Press, 1992)
Cyr, an acclaimed baroque musician as well as a noted scholar, considers "both the boundaries and the freedom that were inherent in baroque performing techniques." Chapter 1 introduces the field of performance practice and its goals, the limits of "authenticity," and the characteristics of baroque sound